A reference-component coordinate system approach to model the mass transfer of a droplet with binary volatiles. Issue 2 (23rd January 2023) - Lim, Kian Siang; Adhikari, Benu; Xiao, Jie; Chen, Xiao Dong; Selomulya, Cordelia; Woo, Meng Wai
Abstract: A theoretical framework based on the reference-component centered coordinates was modified to enable the prediction study of the simultaneous absorption and evaporation of droplets consisting of two volatiles. A new equation of Robin boundary condition was imposed at the droplet-ambience interface, coupling with a new numerical scheme for solution. Experimental validation was performed with the following situations: evaporation of single pure droplet and bicomponent droplet, and simultaneous absorption and evaporation of droplet. The model predicted the mass profiles reasonably well for droplet evaporation while over-prediction was found for the case of simultaneous absorption and evaporation of droplet. Further preliminary evaluation has found the necessity to encounter the phenomenon of mass flux depression when predicting the simultaneous absorption and evaporation of droplet. This will provide a potential predictive tool for the processes which involves droplet absorption, such as antisolvent-vapor precipitation and gas scrubbing.